PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. EMSONIC INDONESIA - Inke Juliani; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The purpose of this study was to determine the effect of training and work discipline to performance of employees at PT. Emsonic Indonesia. The research data used a questionnaire which distributed to respondents and sample was used in this research, using a random sampling technique with a total sample of 65 people. The data analysis method was used in this research with simple and multiple regression analysis. The results showed that training and work discipline had a positive and significant effect to performance of employees at PT. Emsonic Indonesia, The training variable has a more dominant influence than the work discipline variable in influencing the performance of the employees at PT. Emsonic Indonesia.